Analisis Kelayakan Investasi Pabrik Bioethanol Dari Molase Tebu Berkapasitas 100.000 Kl/Tahun di Bojonegoro dan Sensitivitasnya Terhadap Perubahan Harga Bahan Baku dan Harga Jual Produk - Reksa Wijaya Martin; Dedy Setyo Oetomo; Asep Hermawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Indonesia's mandatory bioethanol-blending program faces a substantial domestic supply gap, with demand projected to grow from 478,358 KL in 2026 to 1,170,453 KL by 2040. This study examines the investment feasibility of establishing a 100,000 KL/year sugarcane-molasses bioethanol plant in Bojonegoro and its sensitivity to changes in raw-material and selling prices. A quantitative descriptive approach was applied using secondary data from BPS, ESDM, P3GI, and scientific literature. Financial feasibility was assessed through NPV, IRR, Payback Period, and BEP. The base-case scenario yields an IRR of 14.13% (MARR 10%), NPV of IDR 322.45 billion, and a 6-year payback period. Under a sensitivity scenario combining higher molasses prices and lower selling prices, IRR declines to 13% yet remains feasible, with NPV of IDR 70.98 billion and a BEP of 50,000 KL/year. The project is therefore feasible and reasonably resilient to market price fluctuations.